Problem Konsentrasi Belajar Siswa di Era Digital: Dampak Intensitas Bermain Game terhadap Konsentrasi Belajar - Humairo’, Warda El (Maliki Interdisciplinary Journal, 2025)
This study examines how the intensity of digital game play affects students’ attention and concentration in today’s technological era. Rapid technological developments have made games increasingly accessible, leading many students to spend long hours playing each day. High-intensity gaming causes the brain to become accustomed to receiving rapid and repeated stimuli, ultimately reducing students’ ability to maintain focus while studying. This condition makes them more easily distracted and experiences mental fatigue during the learning process. The study was conducted through a literature review analyzing various relevant sources and studies. The results indicate that long gaming duration, high frequency of play, and the emotions that arise during play significantly influence students’ concentration levels. However, certain types of games can also improve cognitive abilities when used wisely and in a controlled manner. The findings of this study emphasize the importance of moral education to help students manage their time, control themselves, and maintain a balance betweet gaming and learning activities.